1998
DOI: 10.1128/aac.42.7.1537
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Susceptibilities of 27 Rickettsiae to 13 Antimicrobials

Abstract: The MICs of 13 antibiotics (doxycycline, thiamphenicol, rifampin, amoxicillin, gentamicin, co-trimoxazole, ciprofloxacin, pefloxacin, ofloxacin, erythromycin, josamycin, clarithromycin, and pristinamycin) were determined for 27 available rickettsial species or strains. We used two in vitro cell culture methods described previously: the plaque assay and the microplaque colorimetric assay. Our results confirm the susceptibilities of rickettsiae to doxycycline, thiamphenicol, and fluoroquinolones. Beta-lactams, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
94
2
5

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 196 publications
(106 citation statements)
references
References 45 publications
5
94
2
5
Order By: Relevance
“…Rickettsia are naturally resistant to ␤-lactams, aminoglycosides and co-trimoxazole. The typhus group is susceptible to erythromycin, whereas the spotted fever group is not [19,20] (Table 1). …”
Section: Overview Of Natural Antibiotic Susceptibility Among Intracelmentioning
confidence: 98%
See 2 more Smart Citations
“…Rickettsia are naturally resistant to ␤-lactams, aminoglycosides and co-trimoxazole. The typhus group is susceptible to erythromycin, whereas the spotted fever group is not [19,20] (Table 1). …”
Section: Overview Of Natural Antibiotic Susceptibility Among Intracelmentioning
confidence: 98%
“…In the majority of rifampicin-resistant isolates, mutations occurred within an 81-bp hotspot region (the rifampicin resistance-determining region (RRDR), codons 507-533 according to E. coli numbering) in the rpoB gene [4,107]. Previously, Rolain et al [19] found that susceptibility to rifampicin varied, with R. prowazekii, R. typhi, Rickettsia canada, Rickettsia bellii and most SFG rickettsiae being susceptible to rifampicin, whilst the Rickettsia massiliae subgroup (R. massiliae, Rickettsia montana, Rickettsia rhipicephalus and Rickettsia aeschlimannii) were more resistant to rifampicin. Drancourt and Raoult [108] investigated the genetic basis for natural rifampicin resistance in representatives of the TG and the two SFG subgroups of rickettsiae by sequence analysis of the rpoB gene.…”
Section: Rifampicinmentioning
confidence: 98%
See 1 more Smart Citation
“…Lovastatin and pravastatin were purchased from Sigma-Aldrich (Saint-Quentin Fallavier, France) [7]. Lovastatin was hydrolysed as described elsewhere [8] and a stock solution (1 g/L) was stored at −20 • C until use.…”
Section: Methodsmentioning
confidence: 99%
“…Auch Fluoroquinolone und Makrolide (insbesondere Josamycin) haben nach verschiedenen Studien eine gute Wirksamkeit [83]. Eine Eindosistherapie mit 200 mg Doxycyclin hat sich für die Therapie des epidemischen Fleckfiebers in Afrika bewährt [74].…”
Section: Therapie Und Prophylaxeunclassified